Paradox of the Consumer: Case Study on MSMEs in Pacitan Regency (MSME Case Study in Lorok Wiroyo Village, Ngadirojo District, Pacitan Regency, East Java) - et. al., R. Adjeng Mariana Febrianti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the influence of price fairness and employee satisfaction on customer satisfaction with service delivery as an intervening variable in Batik MSMEs in Pacitan. This study used path analysis with of SPSS 23 software. The sample in this study as many as 68 people incidentally. The conclusion in this study is that variable price fairness and employee satisfaction affect customer satisfaction with service delivery as intervening variables. This research was conducted to find out aspects in measuring customer satisfaction which is closely related to the performance of MSMEs especially in the city of Pacitan in the batik sector, and also emphasizes the importance in providing prices and quality of services provided by employees to obtain customer satisfaction to ultimately generate loyalty.